2020
DOI: 10.1111/ppc.12661
|View full text |Cite
|
Sign up to set email alerts
|

State anxiety levels of nurses providing care to patients with COVID‐19 in Turkey

Abstract: This study investigates the state anxiety levels of nurses providing care to patients with coronavirus disease-2019 (COVID-19) in Turkey.Design and Methods: This cross-sectional study is based on the COVID-19 pandemic situation. The State-Trait Anxiety Inventory was used to collect the study data.Findings: Nurses' state anxiety levels were high (51.51 ± 9.94). Participants evaluated for state anxiety were female; who were married; worked in intensive care units; were service nurses, having more professional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 22 publications
4
23
0
11
Order By: Relevance
“…There were 40 studies which reported on data regarding stress, using five different type of scales which were Depression-Anxiety-Stress Scale-21 (DASS-21), Safety Attitudes Questionnaire (SAQ), Perceived Stress Scales (PSS), Stanford Acute Stress Reaction Questionnaire (SASRQ), and State and Trait Anxiety Inventory (STAI) [ 30 , 31 , 39 , 56 , 59 , 77 , 78 , 91 , 92 , 99 – 102 , 104 , 106 , 107 , 113 , 120 , 123 , 124 , 127 , 129 133 , 138 , 140 , 141 , 143 , 144 , 150 , 152 , 153 , 155 , 160 , 161 , 164 , 165 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 40 studies which reported on data regarding stress, using five different type of scales which were Depression-Anxiety-Stress Scale-21 (DASS-21), Safety Attitudes Questionnaire (SAQ), Perceived Stress Scales (PSS), Stanford Acute Stress Reaction Questionnaire (SASRQ), and State and Trait Anxiety Inventory (STAI) [ 30 , 31 , 39 , 56 , 59 , 77 , 78 , 91 , 92 , 99 – 102 , 104 , 106 , 107 , 113 , 120 , 123 , 124 , 127 , 129 133 , 138 , 140 , 141 , 143 , 144 , 150 , 152 , 153 , 155 , 160 , 161 , 164 , 165 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, 5 studies reported data on fear, using five different scales which were Fear of Coronavirus 2019 Scale (FCV-19S), Fear Scale for Healthcare Professionals (FS-HPs), Chinese Classification and the Diagnose Criterion of Mental Disorder (CCMD-3), Numerical rating scale (NRS), and State and Trait Anxiety Inventory (STAI) [ 33 , 58 , 107 , 145 , 158 ]. Besides, two studies that reported on low resilience data were using the Connor-Davidson Resilience Scale (CD-RISC) as screening tool [ 11 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…The STAI has recently been used in COVID-19 settings. A study used the STAI to investigate the state anxiety level of nurses offering care for COVID-19 patients in Turkey [44]. Another study adopted it to explore differences in anxiety among adults in the United Kingdom in the context of COVID-19 [45].…”
Section: Stai-cmentioning
confidence: 99%
“…The score of either state anxiety or trait anxiety ranges from 20 to 80. According to the score, people can be divided into 4 groups: no anxiety (≤20), mild anxiety (21-39), moderate anxiety (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and severe anxiety (60−80) [22].…”
Section: Stai-cmentioning
confidence: 99%
“…Foram encontradas 1.249 publicações, cuja aplicação de filtros, exclusão de duplicatas e leitura completa gerou uma amostra de 18 artigos, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Ressalta-se que os estudos analisados foram investigações de natureza quantitativa e descritiva, classificados como nível de evidência 4, ou seja, são estudo com delineamento não experimental como pesquisas descritivas correlacionais e/ou qualitativa como estudos de caso. 30 Observou-se a existência de seis repercussões para a saúde mental dos profissionais de enfermagem atuantes na linha de frente do enfrentamento à Covid-19, a citar: ansiedade, depressão, estresse, transtorno de estresse pós-traumático, transtornos mentais do sono e Burnout.…”
Section: Resultados Resultados Resultados Resultadosunclassified